To evaluate a function at a given input, you have to substitute every occurrence of the variable with that particular value.
So, for the first function, you have
![T(x) = -x-2 \implies T(-4) = -(-4)-2 = 4-2 = 2](https://img.qammunity.org/2019/formulas/mathematics/middle-school/hyvij5tc597qghir835e9x5bvlzw3kvw74.png)
The name of the variable is obviously irrelelvant, so the same goes for the second function:
![w(x) = 14-6x \implies w(-3) = 14-6\cdot(-3) = 14 + 18 = 32](https://img.qammunity.org/2019/formulas/mathematics/middle-school/mdaq3gtvk9n8owjp1t5ml9zkalena34kwg.png)